2016
DOI: 10.1002/mus.24931
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between electromyography and quantitative ultrasonography of facial muscles in patients with facial palsy

Abstract: Quantitative ultrasound of facial muscles helps confirm the results of facial EMG and is of particular additional value in the first 14 days after onset when the reliability of EMG is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The authors found early signs of re‐myelinisation in EMG while clinical improvement was delayed and thus muscle function did not directly correlate with EMG measurements. Although EMG is a reproducible method to assess muscle re‐innervation, results do not obligatorily correlate to the actual movement of the muscle, but rather with the ability to transmit an action potential without actual muscle contracture (Volk, Leier, & Guntinas‐Lichius, ). Furthermore, painstaking placement of several electrodes is necessary, further limiting its applicability.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found early signs of re‐myelinisation in EMG while clinical improvement was delayed and thus muscle function did not directly correlate with EMG measurements. Although EMG is a reproducible method to assess muscle re‐innervation, results do not obligatorily correlate to the actual movement of the muscle, but rather with the ability to transmit an action potential without actual muscle contracture (Volk, Leier, & Guntinas‐Lichius, ). Furthermore, painstaking placement of several electrodes is necessary, further limiting its applicability.…”
Section: Discussionmentioning
confidence: 99%
“…4 The diameter of the orbicularis oculi ( Figure 1) would tell us if it is a denervated muscle with atrophy or a misdirected reinnervated one were you often see an increased diameter compared with the non-paretic site. 5 In addition, the skin itself and the subdermal connection tissue could be directly visualized by high frequency ultrasound. Again, a comparison with the non-paretic site should help to understand what is going on in the weeks and month after a facial paralysis: are there really chronic edemas and contractions of the skin, or can much of the phenomena be explained by the increased permanent muscle activity?…”
Section: Sir Occurrence and Severity Of Upper Eyelid Skin Contracturmentioning
confidence: 99%
“…B-ultrasonography is widely used to measure muscle or other soft tissues and disease diagnosis [ 32 ]. It is a sensitive detection method for facial muscle thickness and safe, non-invasive, simple to operate, and cost-effective [ 33 35 ]. Studies have shown that normal humans have no significant differences in bilateral expression muscle thickness [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%